THE INFLUENCE OF GUIDED READING STRATEGY AND READING MOTIVATION TOWARDS SEVENTH GRADE STUDENTS’ READING COMPREHENSION ACHIEVEMENT ON DESCRIPTIVE TEXTS AT TRI DHARMA JUNIOR HIGH SCHOOL OF PALEMBANG - Suprapto Gunawan; Rusman Roni; Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2020)
This study is concerned with the Influence of Guided Reading Strategy and Reading Motivation towards Students’ Reading Comprehension Achievement. The problems being formulated in this inquiry seek to find out the extent of Guided Reading Strategy, students’ Reading Motivation, and what teaching strategies are suitable to be applied to improve students’ Reading Comprehension Achievement. Finding shows that (1) there was a significant difference in Reading Comprehension Achievement on Descriptive Text between the students who had High Reading Motivation and Low Reading Motivation taught by using Guided Reading Strategy and Conventional Technique. It could be seen the sig (2-tailed) 0.000 was lower than the significant level of 0.05. (2) There were interaction effects of Guided Reading Strategy and students’ Reading Motivation towards students’ Reading Comprehension Achievement. It could be seen from sig (2-tailed) 0.000 was lower than the significant level 0.05, and (3) Guided Reading Strategy can be utilized to promote the reading skill of the students and it contributes to the students’ Reading Comprehension Achievement improvement.